Effect of probiotic-fermented milk containing Lactiplantibacillus pentoses strain HBUAS 53657 on serum glutathione peroxidase activity and pancreatic histopathology in hyperglycemic rats - Rita Yaswir; Eti Yerizel; Netti Suharti; Cimi Ilmiawati (Acta Biochimica Indonesiana, 2024)
Background: Hyperglycemia is characterized by elevated blood glucose levels caused by impaired insulin production or function, leading to oxidative stress. Probiotic-fermented milk containing Lactiplantibacillus pentosus strain HBUAS 53657 (PFM) has antioxidant and antimicrobial properties that may reduce oxidative stress. Objective: This study aimed to investigate the effects of PFM L. pentosus strain HBUAS 53657 on serum glutathione peroxidase (GPx) activity and pancreatic histopathology in hyperglycemic rats. Method: A post-test-only experimental design was conducted using 25 adult male Wistar rats divided into five groups (n = 5 per group): normal control, hyperglycemic control group, and hyperglycemic rats treated with PFM at doses of 1 × 10⁸ CFU/day (P1), 1 × 10⁹ CFU/day (P2), and 1 × 10¹⁰ CFU/day (P3) for 28 days. Serum GPx activity was assessed via spectrophotometry, Langerhans islet area was measured using ImageJ, and islet damage was evaluated using the Ningrum Score. Statistical analysis was performed using One-Way ANOVA and Kruskal-Wallis tests. Results: PFM administration at all doses significantly increased serum GPx activity (p = 0.002), with an optimal dose of 1 × 10⁹ CFU/day (P2). PFM also increased the Langerhans islet area (p = 0.001) and reduced islet damage scores (p < 0.001) in a dose-dependent manner. Conclusion: Probiotic-fermented milk containing Lactiplantibacillus pentosus strain HBUAS 53657 increases serum GPx activity, expands Langerhans islet area, and reduces islet damage in hyperglycemic rats.